ملائشیاکے حلال معیاربرائے خوراک:MS:1500:2019 ائمہ فقہاء کے تناظرمیں سمندری مخلوق کا طائرانہ جائزہ: Halal Food Standards in Malaysia (MS:1500:2019): A Comparative Study of Marine Creatures from a Jurisprudential Perspective - Inayat ur Rahman; Rabia Hina; Hayat Ahmad (Al Manhal Research Journal, 2023)
Malaysia has embraced halal standards comprehensively, taking pioneering strides in this realm. These standards not only provide avenues for the implementation of halal practices but also serve as a pivotal instrument in stimulating the national economy by fostering industrial and artisanal expertise. The standards also offer prospects for consumers' progression. They play a significant role in the international trade arena and facilitate diplomatic interactions with foreign nations. The Shafi'i juridical framework, inclusive of juridical terminologies, principles, consensus, derivation, and evidentiary bases, is enshrined within the Halal Food Standards (MS:1500), guided by the tenets of Imam Shafi'i's jurisprudential doctrine. Given the predominance of the Shafi'i school of thought in Malaysia, it has been established as legal precedent for the convenience of the general populace, consumers, and producers alike. However, the existence of varying juridical opinions leads to inquiries regarding the selection of standards and juridical interpretations to adhere to, thereby presenting challenges to commercial and tourism sectors. This article serves as a guide for such uncertain situations. Marine creatures inhabit a vast and diverse world, comprising numerous forms and species. Neither the Quran nor Hadith specify what should or should not be consumed from this realm. Some scholars have issued fatwas based on the definition of fish, while others have responded using Quranic and Hadith texts. The following paper clarifies these points.